Major legal systems in the world - Ali Mohamed, Ashgar Ali (Malaysian Current Law Journal, 2014)
The application of legal system varies from country to country and is largely shaped by the unique history of a particular country. Generally, the most widespread legal systems in the world are the Civil Law, the Common Law and the Religious Law. This chapter discusses the general characteristics of the above three major legal systems in the world.